Sustainable Housing Using An Innovative Mortarless Interlocking Blockwork System – The Effect Of Palm Oil Fly Ash (Pofa) As An Aggregate Replacement - Nasly, Mohamed Ali; Abu Azam, Md Yassin; Norhaiza, Nordin; Khairunisa, Muthusamy (2011)
With the increase in material costs in the construction industry, there is a need to find more cost saving alternatives material so as to maintain the cost of constructing houses at prices affordable to clients. Universiti Malaysia Pahang in collaboration with industry partner, CCA Systems Sdn Bhd, has developed a building system which incorporates the interlocking load bearing block as its main feature, which consists of three different block types for the frame and wall system. Sustainability can be achieved by using Palm Oil Fly Ash (POFA) and recycled concrete and aggregate related construction waste as aggregates replacement in the interlocking load bearing block.This paper describes POFA as a replacement material in the production of the interlocking load bearing block. A number of mix proportions were tested and the compressive strength of the cube blocks on the 7th day and 28th day showed that POFA at the mix ratio of 1:6:2 and 1:5:3 (cement: sand: POFA) give optimum value of the compressive strength as replacing aggregates that satisfy the required strength to be used for construction of buildings. Using the formulated mixture, interlocking load bearing block is made using the CCA press, the resultant block is tested and the compressive strength is within the required specification for house construction. The design constraints and construction of a cafeteria building using the load bearing interlocking block is also presented.